Human Milk Microbiome and Maternal Postnatal Psychosocial Distress - Browne, Pamela D.; Aparicio, Marina; Alba, Claudio; Hechler, Christine; Beijers, Roseriet; Rodríguez, Juan Miguel; Fernández, Leonides; de Weerth, Carolina (Frontiers in Microbiology, 2019)
Human milk contains many bioactive components, including bacteria, which are transferred to the developing infant through breastfeeding. Milk bacteria appear to, amongst others, originate from the maternal gut. A mother’s postnatal psychosocial distress may alter maternal gut microbiota, which in turn may affect the bacteria present in milk. The aim of this study was to explore whether maternal postnatal psychosocial distress was related to alterations in the relative abundances of specific bacteria and to milk microbial diversity. Healthy mothers (N=77; N=51 with complete data) collected breast milk samples at 2, 6 and 12 weeks postpartum and filled in mood questionnaires on experienced stress, anxiety and depression at 6 weeks postpartum. A metataxonomic approach (16S rRNA gene sequencing (region V3 and V4) using Illumina MiSeq technology) was used to assess bacterial abundances and diversity. For the group as a whole, an increase in diversity of the milk bacterial community was observed during the first 3 months of breastfeeding (Shannon index). This general increase in diversity appears to be explained by an increase of Lactobacillus and other minor genera, together with a decrease in Staphylococcus. With respect to psychological distress and milk microbial composition, no significant differences in the relative abundance of major bacterial genera were detected between women with high (N=13) and low (N=13) psychosocial distress. However, progressive and distinct changes in the content of Firmicutes, Proteobacteria and Bacteroidetes at the phylum level and Acinetobacter, Flavobacterium and Lactobacillus at the genera level were observed in milk samples of women with low psychosocial distress. With respect to milk microbial diversity, high maternal psychosocial distress, compared to low maternal psychosocial distress, was related to significantly lower bacterial diversity in milk at 3 months post-delivery. Anxiety, stress, and depression separately were unrelated to specific bacterial profiles. The current study suggests a potential relation between maternal psychosocial distress and milk microbiota, providing first evidence of a possible mechanism through which post-partum psychological symptoms may affect infant development and health.